A cable health assessment method based on multi-agent and matter-element extension model. (March 2023) - Zhao, Gen; Di, Haibo; Bai, Hao; Lin, Yuxuan
Highlights: Make a comprehensive assessment of cable health status and give maintenance advice. Consider the power quality of the cable and integrate it into the health assessment. The effectiveness of the proposed method is verified by setting up a test platform. Cable health assessment based on matter-element extension model is accurate and rapid. This paper can provide an effective reference for field operation and maintenance. Abstract: It is of great significance for the stable operation of the power system to accurately evaluate the health status of the cable, and then provide a reference for the implementation of condition maintenance. Based on the matter-element extension model, this paper divides different cable health levels, selects the important state quantity of the cable as the evaluation index, assigns different weights to it, and finally obtains the health level of the cable evaluation. The multi-agent plays its role to make the cable health assessment system run well. The calculation example results show that the health assessment model in this paper can effectively assess the health status of cables in different stages of operation, and the assessment results can be used as a reference for the formulation of on-site maintenance strategies. Compared with other assessment methods, the assessment results are more comprehensive and more reliable.